Application of Design Thinking and User Experience Questionnaire (UEQ) in a WooCommerce Based E-Commerce Platform - Ulya Yumna Salsabila; Nava Gia Ginasta; Triantya Wahyu Wiranti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid growth of e-commerce has placed increasing pressure on small and medium-sized enterprises (MSMEs) to adopt user-centered digital platforms that meet evolving consumer expectations. This study aims to design and evaluate the user interface (UI) and user experience (UX) of a WooCommerce-based e-commerce platform using the Design Thinking methodology and the User Experience Questionnaire (UEQ). The research employed a quantitative-descriptive approach, involving 88 respondents drawn from the School of Business and Management at Logistik dan Bisnis Internasional University using the Slovin formula. The Design Thinking process was applied across five iterative stages Empathize, Define, Ideate, Prototype, and Test to generate a High-Fidelity (Hi-Fi) prototype responsive to user needs. UEQ evaluation results indicate that the redesigned platform achieved Excellent ratings for Attractiveness (mean = 1.778) and Dependability (mean = 1.710), Good ratings for Efficiency (mean = 1.776), Stimulation (mean = 1.599), and Novelty (mean = 1.122), and an Above Average rating for Perspicuity (mean = 1.696). These findings confirm that the Design Thinking approach effectively improves UI/UX quality for WooCommerce-based platforms, contributing to enhanced digital adoption among MSMEs. Future research is recommended to extend the evaluation to a broader and more diverse user population.